Exploring the connection between adolescent identity and well-being in vocational scope - Nisa, Khoirun (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2023)
Adolescence is a significant period starting with mental, emotional development and physical development; adolescents experience many problems due to unfulfilled levels of welfare subject. Because the level of youth welfare also measures the progress of a country, a country also has a responsibility to improve the welfare of its youth. For this reason, this study aims to find which adolescent welfare domain subjects need more attention. Research on youth welfare uses the bibliometric analysis method with the help of the VOS Viewer application system using the keyword